Investigation of ferroelectric, piezoelectric and mechanically coupled properties of lead-free (Ba0.85Ca0.15) (Zr0.1Ti0.9)O3 ceramics. (4th July 2019) - Sailaja, P.; Pavan Kumar, N.; Shara Sowmya, N.; James, A.R.; Kumar, Atul; Arockiakumar, R.; Srinivas, A.
ABSTRACT: Lead-free piezoelectric ceramic (Ba0.85 Ca0.15 )(Zr0.1 Ti0.9 )O3 (BCZT) has been synthesised by solid-state sintering method and the effect of grain size on ferroelectric, piezoelectric, dielectric, mechanical and piezo-electro-mechanical properties was systematically studied. The compacted powders were sintered at three temperatures i.e. 1450°°C, 1500°C and 1550°C for an optimised duration of 5 h and they have exhibited well resolved morphotropic phase boundary with an average grain size ranging from 10 to 25 µm. Enhanced piezoelectric charge, d33 ∼ 560 pC/N and voltage, g33 ∼ 14.3 mV m/N coefficients were obtained for the 1450°C sintered BCZT sample. A maximum strain of around ∼0.14% was obtained which is comparable to that of lead-based piezoelectrics. Variation of relative permittivity with temperature revealed that the curves are independent of frequency, indicating the typical relaxor ferroelectric nature of the samples. A systematic study on cyclic loading was performed to evaluate piezo-electro-mechanical coefficients at different loads which showed hysteresis behaviour. High value of elastic modulus (E) and hardness (H) i.e. 262.7 ± 38.1 GPa and 13.7 ± 1.7 GPa were exhibited by samples sintered at 1450°C, which is higher than that of BCZT synthesised by wet-chemical methods. The results are discussed.